An empirical investigation of internet banking in Taiwan - Hsin, Hsin Chang; Mohamad Rizal Abdul Hamid (Institute for Business and Finance Research, LLC, 2010)
This paper investigates Internet banking adoption among Taiwanese bank customers. The paper examines the affect of involvement using TAM (technology acceptance model). From the PII (Personal Involvement Inventory) scales, the results indicate that involvement is significantly influenced by the characteristics of the person, stimulus and the situation. Two sets of regression analysis were conducted for the current study. The first analyze the direct influence of two factors, belief of perceived usefulness and perceived ease of use. The second set investigates the affect of involvement on perceived usefulness and perceived ease of use in determining behavioral intention. The study found perceived usefulness is strongly influenced by high involvement. Likewise, the study found that low involvement is strongly related to perceived ease of use. In determining behavioral intention, both high and low involvement significantly influence perceived usefulness and perceived ease of use, respectively.